Cryptococcal meningitis presenting as acute flaccid paralysis: A case report - Vanessa Correa-Forero; Gabriel D. Pinilla-Monsalve; Jaime A. Valderrama-Chaparro; Pablo Amaya-Gonzalez (Elsevier, 2020)
Cryptococcus is a cosmopolitan fungus with tropism for the nervous system and a higher prevalence of infection in immunosuppressed patients. Neurological compromise caused by this microorganism mainly debuts as a meningeal syndrome (headache, fever, neck stiffness) with predominant encephalic involvement. In this report we present the rare case of a non-HIV patient with flaccid paralysis and peripheral nerve involvement due to crytpococcal meningitis. This is a 53-years-old woman, with a past-medical history of diabetes, who presented with dysarthria, unilateral peripheral facial paralysis, asymmetric ascending quadriparesis, generalized hyporeflexia and urinary retention. Neuroimaging was initially reported as negative for vascular or demyelinating diseases. Electrophysiological studies were performed, and acute flaccid paralysis of undetermined etiology was defined as a temporal clinical diagnosis. Cerebrospinal fluid molecular analysis confirmed the presence of Cryptococcus neoformans var. gatti; posteriorly, antifungal treatment with amphotericin B and fluconazole was started. Polyneuroradiculopathy symptoms significantly improved over the in-hospital stay. In conclusion, spinal cord and peripheral nerve involvement by Cryptococcus is an infrequent cause of acute flaccid paralysis that should be considered in the differential diagnosis even in HIV-negative patients. Keywords: Cryptococcal meningitis, Acute flaccid paralysis, Case report